Evaluation of Antimicrobial bioactive compounds from Endophytic Fungi Isolated from Moringa oleifera - Manal Fathy Hemeda; Zeinab. M.H. Kheiralla; Hoda H. Abo-Ghalia; Mahmoud M. Elaasser; Sahar Yassin Ibrahim (Journal of Scientific Research in Science, 2022)
Endophytic fungi are microorganisms that inhabit the living tissues of their host plants without causing any host loss. They are considered as a continuous natural source of novel bioactive secondary metabolites with potential application in medicine, which are almost same to their host plant. In this study a total of nine endophytic fungal isolates were collected from leaves and stems of Moringa oleifera. Based on the colonization frequency (CF) results, the highest number of isolates was obtained from plant stem, while the least was from leaves. The nine isolates were identified by keeping track of morphological and microscopic observations. Identification of the two antimicrobial potent strains was confirmed by 18S rDNA-based molecular analysis. The nine isolates were found belonging to Chaetomium, Alternaria, Fusarium, Aspergillus, Mycelia, Penicillium and Nigrospora taxa. Among them, Chaetomium taxon was included the highest CF) 40% (. Evaluation of antimicrobial activity documented ethyl acetate fungal extract as the highest effective inhibitor against Gram-negative and Gram-positive bacteria, and Aspergillus fumigatus. Minimum inhibitory concentration (MIC) was examined for the two most potent antimicrobial effective extracts, from Chaetomium laterale and Chaetomium interruptum; it was ranged from 12.5 to 0.39 mg/ml.